Determining the Effectiveness of Zen Technique on Psychological Well-being and Pain in Elderly Residents of Kahrizak Nursing Home - Riazi, Seyedeh Robabeh; Golshani, Fatemeh; Baghdasarians, Anita; Jafari Roshan, Marjan (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective: This study aimed to examine the effectiveness of Zen meditation techniques on psychological well-being and pain in elderly residents. Methods and Materials: The study employed a quasi-experimental design with pre-test, post-test, and follow-up assessments and included both experimental and control groups. A total of 42 elderly residents (20 men and 22 women, aged 65-85) from Kahrizak Nursing Home in Tehran, Iran, in 2023 were randomly assigned to the groups. The experimental group received Zen meditation training over 20 sessions (100 minutes per session, three times a week), while the control group received no intervention. Psychological well-being was assessed using the Ryff Psychological Well-being Questionnaire, and pain levels were measured with the McGill Pain Questionnaire. Data were analyzed using mixed two-factor ANOVA. Findings: Results indicated that Zen meditation training significantly improved psychological well-being in the experimental group compared to the control group, with notable increases in self-acceptance, positive relations, autonomy, and personal growth. However, the effect on pain reduction was less pronounced and not significant compared to controls, although some pain reduction was observed in the post-test and follow-up assessments. Conclusion: Zen meditation training effectively enhanced psychological well-being among elderly participants, suggesting it could be a beneficial intervention for improving mental health in this population. However, the limited effect on pain highlights the need for further investigation and potentially combining Zen meditation with other pain management strategies. The study recommends more extensive longitudinal research to establish the long-term impact of meditation on well-being and pain in diverse elderly populations.